2018
DOI: 10.4110/in.2018.18.e22
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Evidence of and Potential Mechanisms by Which Second-Hand Smoke Causes Predisposition to Latent and Active Tuberculosis

Abstract: Many studies have linked cigarette smoke (CS) exposure and tuberculosis (TB) infection and disease although much fewer have studied second-hand smoke (SHS) exposure. Our goal is to review the epidemiologic link between SHS and TB as well as to summarize the effects SHS and direct CS on various immune cells relevant for TB. PubMed searches were performed using the key words “tuberculosis” with “cigarette,” “tobacco,” or “second-hand smoke.” The bibliography of relevant papers were examined for additional releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 154 publications
1
14
0
Order By: Relevance
“…Patra et al [22] reviewed 12 studies and reported an almost 2-fold increased risk of active PTB from second-hand exposure and an increased risk of latent TB infection (pooled RR 1.67, 95% CI 1.12–2.48). This finding was confirmed in a review by Bai et al (2018) who reported that the susceptibility for latent and active TB among those exposed to second-hand smoke may be singly or in combination due to suppressed anti-TB immunity and enhanced activity of immunosuppressive N2 neutrophils [23]. Second-hand smoke is a growing concern in regions where PTB poses a significant health risk.…”
Section: Discussionsupporting
confidence: 55%
“…Patra et al [22] reviewed 12 studies and reported an almost 2-fold increased risk of active PTB from second-hand exposure and an increased risk of latent TB infection (pooled RR 1.67, 95% CI 1.12–2.48). This finding was confirmed in a review by Bai et al (2018) who reported that the susceptibility for latent and active TB among those exposed to second-hand smoke may be singly or in combination due to suppressed anti-TB immunity and enhanced activity of immunosuppressive N2 neutrophils [23]. Second-hand smoke is a growing concern in regions where PTB poses a significant health risk.…”
Section: Discussionsupporting
confidence: 55%
“…Their next study showed that passive smokers also had an increased risk of developing latent and active tuberculosis. This susceptibility may be due to the increased exposure to the tubercle bacilli from the increased cough seen in smokers, along with suppressed anti-tuberculosis immunity, enhanced activity of immunosuppressive N2 neutrophils or Tregs, or a combination of these factors 21 . Gleeson et al report on human alveolar macrophages in smokers to be attenuated significantly, with consequent impairment of the glycolytic response to M. tuberculosis infection, which is crucial in the early host immune response to the pathogen 22 .…”
Section: Discussionmentioning
confidence: 99%
“…CS exposure weakens the pulmonary immune system [ 5 ], compromising the protective activity of macrophages, resulting in decreased production of proinflammatory cytokines [ 4 ] and recruitment of T cells [ 6 , 7 ]. In the case of Mycobacterium tuberculosis ( Mtb ), smoking-associated immune dysfunction promotes bacterial survival in macrophages [ 8 , 9 ]. Additionally, CS exposure prevents granuloma formation [ 1 , 3 , 6 ], leading to accelerated disease severity and progression [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%